Study of the effect of family communication and function, and satisfaction with body image, on psychological well-being of obese girls: the mediating role of self-esteem and depression - Zabihollah KavehFarsani; Roya Kelishadi; Kioumars Beshlideh (BMC, 2020)
Abstract Background Obesity has become a global problem in childhood and adolescence. The objective of the present study was to investigate the impact of family communication and function, and body image satisfaction, on psychological well-being by considering: the mediating role of self-esteem and depression. Methods In this cross sectional study, 173 obese and overweight female students were selected and evaluated based on body image satisfaction, self-esteem, depression, psychological well-being, functioning, and family Communication. The proposed model was evaluated through structural equation modeling, using AMOS and SPSS software. Results Results showed that family communication and function directly affected adolescents' psychological well-being. In addition, family communication and function, as well body image satisfaction indirectly affected psychological well-being through self-esteem and depression. Conclusion The current finding suggests that the psychological well-being of obese adolescent girls is associated with many factors, including family functioning and communication, body image satisfaction, self-esteem, and depression. The factors identified in this study may be helpful for mental health policy-makers, in planning and implementing preventive and therapeutic intervention programs.